Compassion Fatigue and Compassion Satisfaction Among Nursing Officers - Parul Sharma; Bindu Shaiju; Jahanara Rahman; Dharmander Singh (Indian Journal of Psychiatric Nursing)
Introduction: Nurses make up the largest group of health-care workers, so it is important to rule out compassion fatigue (CF) and compassion satisfaction among nursing officers. Methodology: A descriptive study was adopted, and purposive sampling technique was used. The present study’s sample included 134 nursing officers. The data were gathered in January 2022 using the Structured CF Scale and the Structured Compassion Satisfaction Scale. The data were analyzed using descriptive and inferential statistics. Results: The findings of the research revealed that the majority of the nursing officers had a moderate level of CF in terms of burnout and secondary traumatic stress and moderate level of compassion satisfaction while taking care of patients suffering from COVID-19. The findings of the present study also revealed that there was no significant relationship between CF in terms of burnout and secondary traumatic stress and compassion satisfaction, but a negative and weak correlation was evident. It was found that there was no significant association between CF in terms of burnout with selected demographic variables. It was also found that there was a significant association between CF in terms of secondary traumatic stress with age and there was no significant association between compassion satisfaction with demographic variables. Conclusion: It was found that the majority of nursing officers were highly satisfied with their jobs and they were found to be more compassionate during this pandemic.